Obstructive Sleep Apnea Risk and Subclinical Atherosclerosis in South Asians Living in the United States - Deol, Rupinder (Sleep Health, 2019)
OBJECTIVES: We examined the association between high risk of obstructive sleep apnea (OSA) and subclinical atherosclerosis among South Asians in the United States. DESIGN: A secondary analysis of cross-sectional data. SETTING/PARTICIPANTS: A community-based cohort of 906 men and women participating in the Mediators of Atherosclerosis in South Asians Living in America (MASALA) study. MEASUREMENTS: The Berlin Questionnaire was used to screen for OSA risk. Coronary artery calcium (CAC), common carotid artery intima media thickness (IMT) and internal carotid artery IMT were used as measures of subclinical atherosclerosis. RESULTS: The majority of participants (59%) with high OSA risk had a CAC scores >0 compared to only 41% of participants with low OSA risk (p<.001). The high OSA risk group was older (p=.005), male (p=.04), had higher BMI (p<.001) and had greater common carotid artery IMT (0.96±0.27 mm) and internal carotid artery IMT (1.33±0.42 mm) measurements. Snoring, sleep disordered breathing, and high OSA risk were associated with subclinical atherosclerosis. However, only high OSA risk remained significant in multivariable models that after controlling for demographic and clinical factors that included hypertension, obesity, diabetes and dyslipidemia. CONCLUSIONS: High OSA risk, which includes overlapping comorbidities of hypertension and obesity, was not associated with time living in the US, but was associated with subclinical atherosclerosis markers. These cardiovascular disease risk factors should include evaluation of the spectrum of sleep disordered breathing among all adults, including South Asian men and women.